Distinct roles of Kaposi's sarcoma-associated herpesvirus-encoded viral interferon regulatory factors in inflammatory response and cancer - Baresova, Petra; Pitha, Paula M; Lubyova, Barbora (Journal of virology, 2013)
Kaposi's sarcoma-associated herpesvirus (KSHV) is the etiologic agent associated with Kaposi's sarcoma (KS), primary effusion lymphoma (PEL), and multicentric Castleman disease (MCD). Similar to other herpesviruses, KSHV has two life cycles, latency and lytic replication. In latency, the KSHV genome persists as a circular episome in the nucleus of the host cell and only a few viral genes are expressed. In this review, we focus on oncogenic, antiapoptotic, and immunomodulating properties of KSHV-encoded homologues of cellular interferon regulatory factors (IRFs)--viral IRF1 (vIRF1) to vIRF4--and their possible role in the KSHV-mediated antiviral response, apoptosis, and oncogenicity.
Keywords: Interferons; signální transdukce; apoptóza; Inflammation; Herpesvirus 8, Human; multigenová rodina; zánět; Signal Transduction; Carcinogenesis; lidský herpesvirus 8; interferony; Models, Biological; Multigene Family; virové geny; Viral Proteins; interferonové regulační faktory; Humans; Interferon Regulatory Factors; biologické modely; virové proteiny; karcinogeneze; Genes, Viral; lidé; Apoptosis